Examination of sleep in relation to dietary and lifestyle behaviors during Ramadan: A multi-national study using structural equation modeling among 24,500 adults amid COVID-19 - Khan, Moien A. B.; BaHammam, Ahmed S.; Amanatullah, Asma; Obaideen, Khaled; Arora, Teresa; Ali, Habiba; Cheikh Ismail, Leila; Abdelrahim, Dana N.; Al-Houqani, Mohammed; Allaham, Kholoud; Abdalrazeq, Rand; Aloweiwi, Wahid Sharif; et al. (Frontiers in Nutrition, 2023)
Background: It is estimated that out of the current 2 billion Muslims, around 1.5 billion observe Ramadan intermittent fasting (RIF), distributed over a wide geographical area with versatile cultural, ethnic, social, and economic backgrounds. Sleep is significantly altered during the holy month of Ramadan and is known to have a profound impact on human health. Moreover, sleep is also closely connected to dietary and lifestyle behaviors. Methods: A cross-sectional study design was conducted using an electronic structured, self-administered questionnaire that was disseminated to Muslim populations across 27 countries. The survey was translated into 13 languages. The questionnaire assessed dietary and lifestyle behaviors as independent variables, with three sleep parameters: quality, duration, and disturbance as the dependent variables. In addition, Structural Equation Modeling (SEM) was performed. Results: A total of 24,541 adults were enrolled in the study. During Ramadan, SEM analysis revealed that optimum sleep duration (7-9 hours) was significantly associated with frequently practiced physical activity (PA), and frequently consumed plant-based proteins. Smoking was significantly associated with greater sleep disturbance and lower sleep quality reported during Ramadan. Those with frequent consumption of vegetables, fruits, dates, and plant-based proteins reported better sleep quality. Infrequent use of food delivery and infrequent screen time were also associated with better sleep quality. Conflicting results were found regarding dining in and out in relation to the three sleep parameters. Conclusions: Improving the intake of fruits and vegetables, as well as plant-based food proteins, are important factors that could help improve healthier sleep parameters during the observance of Ramadan fasting. In addition, regular PA, and avoiding smoking are important factors that may contribute to sleep improvement amongst fasting Muslims during Ramadan.